UJI VALIDITAS DAN RELIABILITAS HASIL ANALISIS SWOT STRATEGI PENGEMBANGAN KADASTER MULTIGUNA - Putra, Andriansyah
The concept of multipurpose cadastral is a framework that supports information related to land that is sustainable, available, and comprehensive in every field by integrating the functions of land administration, including land tenure, land valuation, land use, and land development. A multipurpose cadastre is needed to be able to present land information in a complete, fast, and accurate manner in managing land administration. The development of computer technology has become the main vehicle for the modernization of the cadastral system today. The old system was expanded by integrating various functions in an object-based digital cadastral map to improve resource management and support the efficiency of sustainable development. Therefore, an analysis of multipurpose cadastral development strategies and their implementation in Indonesia is needed. This study discusses the validity test with the product-moment correlation method and the reliability test with the cronbach's alpha method on the results of the SWOT (Strength, Weakness, Opportunity, and Threat) analysis of multipurpose cadastral development strategies in Indonesia. The SWOT analysis results obtained will be a reference in making a questionnaire using a likert scale. Questionnaire results that have been obtained are then processed using statistical calculation software applications. Based on the results of validation and reliability testing of all SWOT factors, it is concluded that all SWOT analysis factors used in this study had reach the quantified research criteria. The value of Corrected Item Total Correlation (rcount) on all SWOT analysis factors has a value greater than the rtable (0.367) so that it is declared valid. In the reliability test also obtained that rcritical value greater than ralpha (0.600), so it can be concluded that the four SWOT analysis factors tested were stated to be reliable.